1969
DOI: 10.1103/physrev.183.854
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Analog States and Coulomb Displacement Energies in the (1d52) Shell

Abstract: The (p, t) and (p, 3 He) reactions have been used to locate three previously unknown T~\ isobaric analog states in 19 F, 19 Ne,and 23 Mg, in addition to significantly improving the precision on the energies of the T= f state in 23 Na and the T = 2 states in 20 F and 24 Na. These multiplets all lie within the " (ld m ) shell" in that they have fewer than n=12 nucleons outside 16 0, and r Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The assumed ground-state spin of | + is based on its mirror 23 Ne; other data in the figure are from Hardy et aZ. 7 and Haun and Robertson. 8 The superallowed j3 decay of nuclides in the mass series A = 4^ + 3, T 2 = - § leads to levels in their daughters which are very close to the proton separation energy.…”
Section: Recent Mass Measurementsmentioning
confidence: 99%
“…The assumed ground-state spin of | + is based on its mirror 23 Ne; other data in the figure are from Hardy et aZ. 7 and Haun and Robertson. 8 The superallowed j3 decay of nuclides in the mass series A = 4^ + 3, T 2 = - § leads to levels in their daughters which are very close to the proton separation energy.…”
Section: Recent Mass Measurementsmentioning
confidence: 99%
“…by a level density resolvable within the energy resolution of the system (∼ 60 keV). While there has been a single previous study of the 20 Ne(p, 3 He) 18 F reaction [28], a spectroscopic study of the levels populated in the reaction has not been previously reported. Similar to the 20 Ne(p, d) 19 Ne data, events associated with 3 He ejectiles were selected in software for analysis.…”
Section: Ne(p 3 He) 18 F Analysismentioning
confidence: 99%
“…ref. [6]), and this triplet has therefore been excluded from a shell model analysis of Coulomb displacement energies [6,8]. The admixture of different shells is one of the possible explanations of this anomaly [6].…”
Section: Pacsmentioning
confidence: 99%